Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s10661-015-4730-0
|View full text |Cite
|
Sign up to set email alerts
|

Landscape level estimate of lands and waters impacted by road runoff in the Adirondack Park of New York State

Abstract: Road runoff is understood to be a significant stressor in terrestrial and aquatic ecosystems, yet the effects of this stressor are poorly understood at large spatial scales. We developed an efficient method for estimating the spatial impact of road runoff on lands and waters over large geographic areas and then applied our methodology to the 2.4 million ha Adirondack Park in New York State. We used TauDEM hydrologic modeling and a series of ESRI GIS processes to delineate surface flow downslope of paved roads,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…Positive chloride trends were present in lakes with as little as 1% impervious coverage. This finding is consistent with studies of US streams that found increased chloride concentrations associated with any urban land cover (31) or roads (32,33) and substantiates findings of ecological community thresholds associated with low levels of catchment urbanization (34). Across the NALR, lakes with mean chloride concentrations >1 mg L −1 (mean value of the time series) were more likely to be associated with positive trends in chloride (Fig.…”
Section: Significancesupporting
confidence: 89%
“…Positive chloride trends were present in lakes with as little as 1% impervious coverage. This finding is consistent with studies of US streams that found increased chloride concentrations associated with any urban land cover (31) or roads (32,33) and substantiates findings of ecological community thresholds associated with low levels of catchment urbanization (34). Across the NALR, lakes with mean chloride concentrations >1 mg L −1 (mean value of the time series) were more likely to be associated with positive trends in chloride (Fig.…”
Section: Significancesupporting
confidence: 89%
“…Buffer widths of 100, 200, 300, 400, 500, 1,000, and 1,500 m were chosen based on previous findings, such as those by Kelting et al 29 , who found that >70% of total variation in chloride concentrations in Adirondack Park, NY could be explained by the road density in 320- to 1,280-m buffer zones. Regalado and Kelting 30 used a 100-m buffer as an estimate of vehicular spray distance, and Read et al 31 used a 200-m buffer to understand local drivers on lake characteristics across the United States. We calculated both the percent impervious surface and total road density within buffer zones surrounding each lake as metrics for urban development.…”
Section: Methodsmentioning
confidence: 99%
“…Increased connections come in the form of tile drains and irrigation networks in agricultural systems McIsaac and Hu, 2004) and impervious surfaces in urban environments (DeWalle et al, 2000;Jones et al, 2000). These rapid transport systems readily deliver water and associated material (e.g., nutrients, pollutants, road salts) to the channel network during hydrologic events (Regalado and Kelting, 2015;Yang et al, 2011). This is an area of concern for aquatic ecosystem management in part because the large amount of inorganic nutrients (e.g., nitrogen, N, and phosphate, P) humans apply to the terrestrial environment (Bouwman et al, 2013b;Filippelli, 2008;Vitousek et al, 1997) in the form of fertilizers can be readily transported to rivers, lakes, and other receiving water bodies (Baker and Johnson, 1981;Smith et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%